Circulating choline is associated with coronary artery stenosis in patients with hypertension: A cross‐sectional study of Chinese adults. Issue 11 (23rd September 2020) - Guo, Fei; Qiu, Xueting; Zhu, Yuanting; Tan, Zhirong; Li, Zhenyu; Ouyang, Dongsheng
Abstract: Choline is an important nutrient involved in multiple biosynthesis pathways. However, whether circulating choline levels are associated with the risk of hypertension (HTN) and artery stenosis in HTN remains unknown. We investigated the correlations of plasma choline with HTN and coronary artery injury and explored the utility of plasma choline as a diagnostic biomarker for HTN and artery stenosis. 193 HTN patients and 154 age‐ and sex‐matched healthy controls (CON) were recruited in this study. Fasting plasma choline was detected using liquid chromatography tandem mass spectrometry. Choline levels were significantly higher in HTN without artery stenosis (HTN‐AS) than CON (8.07 [7.19‐9.24] μM vs 7.03 [6.21‐8.13] μM, P  < .01) group and were further upregulated in HTN with artery stenosis (HTN + AS) (8.63 [7.09‐10.59] μM, P  < .01) group. Patients with multivessel disease (MVD) also exhibited higher choline levels than those with single vessel disease (SVD) (8.64 [7.16‐10.55] μM vs 8.04(6.74‐9.38) μM, P  < .01). Increased choline levels were independently associated with the risk of HTN (OR = 1.2, 95% CI: 1‐1.45, P  = .05), HTN + AS (OR = 1.27, 95% CI: 1.09‐1.48, P  < .01), and MVD (OR = 1.16, 95% CI: 1.02‐1.31, P  = .02) after adjustment for multiple risk factors. Receiver operating characteristic (ROC) analysis showed that choline had an area under curve (AUC) score of 0.69, 0.67, and 0.63 in determining HTN, HTN + AS, and MVD. In conclusion, higher choline levels were associated with increased risk of HTN and artery stenosis in hypertensive patients.